Духовный реализм как творческий метод мистической дилогии Всеволода Соловьева - Никольский, Евгений; Нікольський, Євген; Nikolskiy, Eugene (Східноєвропейський національний університет ім. Лесі Українки, 2014)
В статье рассмотрена специфика мистической дилогии (романы «Волхвы» и «Великий Розенкрейцер») Всеволода Соловьева (1849−1903) с точки зрения художественного метода. Автор приходит к выводу, что данные произведения следует отнести к явлению духовного реализма, потому что сотериологическая пробле-матика романов, изображение духовного восхождения главного героя от мрака гордыни к свету христианской любви показывают, что при создании произведений Всеволод Соловьев опирался на традиции святоотеческого богословия. Для выяснения авторской позиции писателя произведено сопоставление концептуально важных фрагментов текста и творений святого Феофана Затворника. У статті розглянуто специфіку містичної дилогії (романи «Волхви» та «Великий Розенкрейцер») Всеволода Соловйова (1849−1903) з погляду художнього методу. Зроблено висновок, що проаналізовані твори слід віднести до явища духовного реалізму, оскільки сотеріологічна проблематика романів, зображення духовного сходження головного героя від мороку гордині до світла християнської любові показують, що при написанні творів Всеволод Соловйов спирався на традиції святоотцівського богослов’я. Для з’ясування авторської позиції письменника проведено зіставлення концептуально важливих фрагментів тексту і творінь святого Феофана Затворника. The article is devoted to the specifics of the mystical novels (novels “Wizards” and “The Great Rosecroix”) Wsevolod Solovyov (1849−1903) from the point of view of the artistic method. The author comes to the conclusion that the work should be attributed to the phenomenon of spiritual realism, because the religious problems of the novels, the image of the spiritual ascent of the main hero of the darkness of pride to the light of christian love, show that for the creation of works of Wsevolod Soloviev relied on the traditions of patristic theology. For finding-out of the author’s position of the writer was a comparison of a conceptually important pieces of text, and the works of st. Theophanes The Recluse.
Spiritual Realism as a Creative Method of Mystical Novels Wsevolod Solovyov
Keywords: духовный реализм; полемика с оккультизмом; духовное становление личности; историческая проза; религиозно-философская позиция писателя; духовний реалізм; полеміка з окультизмом; духовне становлення особистості; історична проза; релігійно-філософська позиція письменника; spiritual realism; polemics with the occult; spiritual development of personality; historical prose; religious-philosophical position of the writer